FPHP 2023; events & activities / Hashim Fadzil Ariffin - Ariffin, Hashim Fadzil (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Welcome to the latest edition of the FPHP Bulletin, where wecome together under the theme " Together We Make It Great ." In this issue , we celebrate the power of unity and collaboration, showcasing the remarkable achievements and collective efforts of our FPHP community . As we navigate through the currents of change and progress, it's our shared commitment to excellence that propels us forward. Our contributors have woven tales of inspiration, innovation, and dedication that demonstrate the strength of our collective endeavors . From stories of teamwork and partnerships to the significant milestones we've achieved together, this issue serves as a testament to what we can accomplish when we work hand in hand.